(3WQb GdEMUGA (B:s (3JWHjbGJ EbJUGOjI hEOGQjI HGSJNOGe (BSPSS /s - (3GdYJhe, Tajbs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2005)
(3Yde GdEMUGA hGdHMK GdYdej(B- (3hUa GdHjGfGJ GdEMUGFjI hHYV GdQehR hGdeUWdMGJ(B- (3ebGjjS GdJhSW Ch ebGjjS GdfRYI GdeQcRjI(B- (3ebGjjS GdJTJJ(B- (3GdYRhe hGdEdJhGA hGdJaQWM(B- (3GdEMJeGd hJWHjbGJg(B- (3GdeJZjQGJ GdYThGFjI hGdJhRjYGJ GdEMJeGdjI(B- (3JhRjY GdeYGjfI hfXQjI GdfRYI GdeQcRjI hJhRjYGJ GdYjfGJ GdUZjQI(B- (3GdJbOjQ GdEMUGFj(B- (3GNJHGQ GdaQhV GdEMUGFjI(B- (3GdEQJHGW hGdEfMOGQ GdNWj GdHSjW(B- (3JMdjd GdEfMOGQ GdeJYOO(B- (3JMdjd GdJHGjf(B.s
Keywords: (3GdEMUGA GdeGdjs; (3GdEOGQIs; (3GdEbJUGOs